Risk Aversion, Behavioral Finance and Green Bonds for the Sustainability of Environmental Assets in Peru - Coayla, Edelina (Journal of Economics and Behavioral Studies, 2021)
The study objective is to investigate the relationship between behavioral finance and the decision to invest in green bonds for the sustainability of environmental assets in Peru. A survey with behavioral questions was applied to a sample of 54 respondents between July and October 2019. Spearman’s rank correlation, independence tests, and logistic regression were used. Significant negative correlations were found between the level of education and risk aversion, and between age and risk aversion. A negative relationship was found between risk aversion and the feeling of comfort when investing in stock market instruments such as green bonds. Aversion to a loss in investment decisions was validated; most people choose low-risk fixed income instruments despite feeling safe investing in stocks. According to the logistic regression, the decision to invest in green bonds to improve environmental quality is explained by the variables “green bond rating” and “feeling of comfort (satisfaction) investing in green bonds.”